1995
DOI: 10.1007/bf00193166
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of heterozygosity at the deleted in colorectal carcinoma gene locus and its association with histologic phenotypes in breast carcinoma

Abstract: Loss of heterozygosity (LOH) at the deleted in colorectal carcinoma gene (DCC), a tumour suppressor gene that encodes a protein with high homology to the neural cell adhesion molecule, was investigated in 42 surgical specimens of primary breast carcinoma. LOH was analysed in breast carcinoma by amplifying the DNA, spanning a variable number of tandem repeats site and a restriction fragment length polymorphism site within DCC, using the polymerase chain reaction (PCR). Cell sorting was used to enrich carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…For breast cancer, LOH at the APC was detected in 38.0% of informative cases by Kashiwaba et al 26 and 28.0% of cases by Thompson et al 27 We found that APC protein expression was reduced or lost in 40.7% cases which was similar to Kashiwaba's ®nding. However, no statistically signi®cant difference was found between the histological morphology nor the staging of both colorectal carcinoma and breast cancer.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For breast cancer, LOH at the APC was detected in 38.0% of informative cases by Kashiwaba et al 26 and 28.0% of cases by Thompson et al 27 We found that APC protein expression was reduced or lost in 40.7% cases which was similar to Kashiwaba's ®nding. However, no statistically signi®cant difference was found between the histological morphology nor the staging of both colorectal carcinoma and breast cancer.…”
Section: Discussionsupporting
confidence: 80%
“…51.7%) was found in 15 out of 29 breast cancer. 26 In addition, Wakita et al had used the immunohistochemical method to show the decrease in expression of DCC (51.0%). In this study, 55.6% of breast cancer cases had shown reduced or loss of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of DCC arose from questions about the loss of heterozygosity in chromosome 18q in colorectal tumors and other malignant conditions. 8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Analysis of the loss of heterozygosity can-*Plus-minus values are means Ϯ SD. †The P value was calculated by Fisher's exact test for the comparison of the DCC-positive group with the DCC-negative group.…”
Section: Discussionmentioning
confidence: 99%
“…Since DCC was discovered by Vogelstein et al in 1990(Fearon et al, 1990, there have been many reports describing the high frequency of LOH at the DCC locus in the colon cancer tissues lacopetta et al, 1994;lino et al, 1994), and in many other cancers (Hohne et al, 1992;Miyake et al, 1994;Murty et al, 1994;Kashiwaba et al, 1995;Cho et al, 1996). DCC has been evaluated as a tumour-suppressor gene candidate on chromosome 18 in colorectal cancers (Thiagalingam et al, 1996).…”
Section: Discussionmentioning
confidence: 99%